Diversity of the genus Trichomycterus Valenciennes, 1832 (Siluriformes, Trichomycteridae) in the Rio Doce basin: a systematic study integrating phenotypes, DNA and classical taxonomy - Reis, Vínicius José Carvalho (2018)
The diversity of the genus Trichomycterus Valenciennes 1832 in the Rio Doce basin is investigated using conventional and modern morphology and DNA analyses. The work is presented in two Chapters. Chapter One, entitled Diversity of the genus Trichomycterus Valenciennes, 1832 (Siluriforms, Trichomycteridae) in the Rio Doce basin: a systematic study integrating phenotypes, DNA and classical taxonomy integratively analyzes specimens of the genus from the entire Rio Doce drainage and adjacent basins, both from available world-wide collections and from active sampling efforts. A combination of phenotypic and DNA (COI barcoding analysis) provides evidence for the existence of 14 species in the basin, 10 of which are new: T. alternatus Eigenmann, 1917; T. argos Lezama et al., 2012; T. astromycterus sp. nov.; T. barrocus sp. nov.; T. brucutu sp. nov.; T. brunoi Barbosa & Costa, 2010; T. immaculatus (Eigenmann & Eigenmann, 1889)] T. illuvies sp. nov.; T. melanopygius sp. nov.; T. ipatinguensis sp. nov.; T. pussilipygius sp. nov.; T. sordislutum sp. nov.; T. vinnulus sp. nov; and T. tantalus sp. nov. . In addition, a lectotype is designated for T. immaculatus and the species is considered as a senior synonym of Trichomycterus pradensis Sarmento-Soares et al., 2005. Although remarkable, such increase in species number of Trichomycterus in a single drainage matches similar recent increments in some other Southeastern Brazilian basins, such as the Paraíba do Sul and Iguaçu. The kind of differentiation among species herein recognized varies, with some of them being well-differentiated in morphology but not in barcoding data, and others showing the opposite phenomenon. The geographical distribution of each of the 14 species is plotted in the Rio Doce basin. The wide geographical distribution of some species (T. alternatus and T. immaculatus) is explained against data from geomorphological processes and comparative information on their biology. Chapter two, The type specimens of Trichomycterus alternatus (Eigenmann, 1917) and T. zonatus (Eigenmann, 1918), with elements for future revisionary work (Teleostei, Siluriformes, Trichomycteridae) focuses on the complex taxonomy, nomenclature and type material status of T. alternatus and T. zonatus. The type series of the two species are analyzed in detail, both in morphology and locality data. Osteological information was obtained with conventional and a new technique of radiographic stereo-triplets. Our new data elucidates their species distinctiveness, diagnostic characteristics, type localities and show that T. zonatus does not occur in the Rio Doce basin.